Coronary events and exposure to environmental tobacco smoke: a case-control study from Australia and New Zealand. Issue 1 (1st March 1998) - McElduff, Patrick; Dobson, Annette J; Jackson, Rod; Beaglehole, Robert; Heller, Richard F; Lay-Yee, Roy
Abstract : OBJECTIVES: To estimate the relative risk of coronary heart disease (CHD) associated with exposure to environmental tobacco smoke (ETS). DESIGN: Population-based case-control study. SUBJECTS: Cases were 953 people identified in a population register of coronary events, and controls were 3189 participants in independent community-based risk factor prevalence surveys from the same study populations. SETTING: Newcastle, Australia and Auckland, New Zealand. MAIN OUTCOME MEASURES: Acute myocardial infarction or coronary death. RESULTS: After adjusting for the effects of age, education, history of heart disease, and body mass index, women had a statistically significant increased risk of a coronary event associated with exposure to ETS (relative risk (RR) = 1.99; 95% confidence interval (CI) = 1.40–2.81). There was little statistical evidence of increased risk found in men (RR = 1.02, 95% CI = 0.81–1.28). CONCLUSION: Our study found evidence for the adverse effects of exposure to ETS on risk of coronary heart disease among women, especially at home. For men the issue is unclear according to the data from our study. Additional studies with detailed information on possible confounders and adequate statistical power are needed. Most importantly, they should use methods for measuring exposure to ETS that are sufficiently accurate to permit the investigation of dose-response relationships.